Characteization of Agricultural production systems in the Guarguallá-Licto irrigation project, canton Riobamba, province of Chimborazo - Verdezoto Vargas, Victor (2018)
This research arises from the need to identify and characterize the rural typologies and agricultural production systems predominant in the Guarguallá - Licto irrigation project, located in Licto parish, canton Riobamba, Chimborazo province. Its general objective was to identify the agricultural production systems for the formulation of intervention strategies differentiated by peasant system and typology, which would improve the economic income of the communities. The target population consisted of 900 peasant families, where all the agricultural productive units (UPA) were chosen at random, and a simple random sample was developed. The surveys were applied to 133 small rural producers in 14 communities, what allowed the collection of relevant information from 30 identified variables of agrosocioproductive characteristics. As a result, it was obtained that 87.22% of small producers make up the largest group called Typology 1 within Production System 1. The 12.78% is distributed among small groups that belong to Production System 2. The proposed intervention for these two production systems focuses on the unification of scattered plots and sustainable agriculture practices